Prevalence of orofacial trauma in soccer players of a Brazilian club - Barbara Capitanio de Souza; Larissa Leci Fernandes; Debora Magalhaes Barreto; Cornelis Robert Springer (Journal of Health Sciences, 2019)
Introduction: The objectives of the study were to evaluate the prevalence of orofacial injuries in soccer players of a Brazilian club, considering the category, the position in the field, and the most affected anatomic site, through medical records.